Inflation measurement with high frequency data - Kevin J. Fox; Peter Levell; Martin O'Connell (Institute for Fiscal Studies (IFS), 2023)
The availability of large transaction level datasets, such as retail scanner data, provides a wealth of information on prices and quantities that national statistical institutes can use to produce more accurate, timely, measures of inflation. However, there is no universally agreed upon method for calculating price indexes with such high frequency data, reflecting a lack of systematic evidence on the performance of different approaches. We use a dataset that covers 178 product categories comprising all fast-moving consumer goods over 8 years to provide a systematic comparison of the leading bilateral and multilateral index number methods for computing month-to-month inflation.
Keywords: C43; E31; 330; Consumer price index (CPI); chain drift; multilateral indexes; scanner data